Theory of ultrafast quasiparticle dynamics in high-temperature superconductors : the dependence on pump fluence - Prasankumar, Rohit P. (2013)
We present a theory for the time-resolved optical spectroscopy of high-temperature superconductors at high excitation densities with strongly anisotropic electron-phonon coupling. A signature of the strong coupling between the out-of-plane, out-of-phase O-buckling mode (B1g) and electronic states near the antinode is observed as a higher-energy peak in the time-resolved optical conductivity and Raman spectra, while no evidence of strong coupling between the in-plane Cu-O-breathing mode and nodal electronic states is observed. More interestingly, it is observed that under appropriate conditions of pump fluence, this signature exhibits a reentrant behavior with time delay, following the fate of the superconducting condensate.